Pertanggungjawaban Pidana bagi Anak Pengendara Mobil yang Menyebabkan Kematian Pengguna Jalan (Studi Putusan No. 26/PID.Sus-Anak/2019/PN.Jayapura) - Saputra, Rizky Robbi; Indawati, Yana (Sultan Jurisprudence: Jurnal Riset Ilmu Hukum, 2022)
Legal responsibility between adults and children is certainly different. Children violate legal provisions, they must still be held legally responsible by taking into account the best interests of the child. Diversion is the right treatment to be applied to children as a crime in accordance. In the case in Decision No. 26/PID.Sus-Anak/2019/PN.Jayapura there was a child as the perpetrator of a traffic accident, resulting in the victim's death. The judge instead imposed a sentence of 1 year against the perpetrator. Based on this, of course it becomes a legal problem and should be explored regarding the judge's consideration in the decision. The appropriate form of criminal liability should also be explored. This type of research is normative juridical, with a statutory, conceptual, and regulatory approach, and uses the literature study method. The results showed that the judge handed down the decision based on the consideration that the perpetrator's actions complied with Article 310 Paragraph (4) UU LLAJ. The form of criminal responsibility for children as perpetrators is to pay attention to the UU SPPA, which is in the form of diversion in accordance with the UUPA. Restorative values are put forward in handling the case, for the sake of the child's psyche and survival, losses that can still be handled properly, and also minimize the emergence of community or other criminal acts committed by children as perpetrators which is certainly disturbing. Parents have an important role in this.